Prevalence of double burden of malnutrition among urban school going Bodo children aged 5-11 years of Assam, Northeast India (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Overweight, obesity and thinness are major important determinants of adverse public health issues, which lead to the development of several preventable non-communicable disease and ill-health conditions.Aims and objectives: The objectives of the present study were to assess the prevalence and certain socioeconomic and demographic factors affecting the double burden of malnutrition among urban children of Assam, Northeast India.Materials and Methods: The present cross-sectional study was undertaken among 1017 (528 boys; 489 girls) the tribal Bodo children aged 5-11 years of Udalguri district of Assam, Northeast India by using the stratified random sampling method. Height and weight were obtained using standard anthropometric procedures and Body Mass Index (BMI=weight/height2, kg/m2) was calculated. The prevalence of thinness, overweight and obesity was assessed by using recently proposed age-sex specific BMI based international classification/reference of Cole et al.Results: The overall prevalence of overweight (boys 13.45%; girls 11.04%) was found slightly greater than obesity (boys 11.93%; girls 10.02%). The result showed that 10.23% and 11.04% were suffering from thinness among boys and girls, respectively. Binary logistic regression analysis showed that the odds were found to be significantly associated with ≤ 10th standard mothers' education, 1st earning head and Rupees
Keywords: Anthropometry; Malnutrition; Public Health; Child Health Status; Nutrition Assessment; Obesity